Exogenous Proline and Glycinebetaine Mitigate the Detrimental Effect of Salt Stress on Rice Plants - Sobahan, Muhammad Abdus; Akter, Nasima; Murata, Yoshiyuki; Munemasa, Shintaro (Science, Engineering and Health Studies, 2016)
Exogenous application of proline and glycinebetaine (hereafter betaine) is often regarded as a shotgun approach for the protection and survival of plants under abiotic stresses including salinity. Here, we investigated effects of proline and betaine on hydrogen peroxide (H2O2), malondialdehyde (MDA) and transpiration rate in salt-stressed rice plants. Generally, salt stress increased H2O2and lipid peroxidation as indicated by MDA content and decreased transpiration rate in rice plants. The exogenous application of proline and betaine decrease H2O2and MDA contents and increase transpiration rate in salt-stressed rice plants. It is suggested that exogenous proline and betaine mitigate the detrimental effects of salt stress by reducing H2O2and lipid peroxidation levels and by increasing transpiration rate in rice plants.